Agency In Truancy: Runaway Slaves and the Power of Negotiation In the United States, 1736-1840 - North, Colin (Université d'Ottawa / University of Ottawa, 2015)
Historians of the American South have been diverse in their descriptions of the master-slave relationship over the last half-century, and have engaged in lengthy discussions in an attempt to answer the intricate question of what life was like between slaves and their masters. The phenomenon of slave runaways has perhaps offered the most convincing evidence of the troubles on southern plantations, which has been used in recent decades to emphasize negotiation and agency in the shaping of master-slave relations. The last twenty years have been consequently marked by a plethora of studies that accentuate non-traditional slave holding as it becomes clearer that masters had to compromise with their human chattel. Through an examination 9,975 runaway slave advertisements and 943 testimonies of former slaves, this study illustrates how black bondsmen absented themselves so to negotiate the terms of their working and living conditions. It traces the acts of individual slave runaways in place of broader generalizations that have for a long time contributed to some of the myths and legends of American slavery through examination of the many reasons that slaves chose to stay in bondage.
Keywords: Slave; Agency; Power; Negotiation; United States